THEORETICAL AND PRACTICAL PROBLEMS OF URBANIZATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article deals with issues such as presidential decrees and resolutions, administrative territorial issues, command, paperwork, corruption, mistrust of management, familiarity, improper documentation, illegal construction, unemployment, quality education, quality medicine, integration of rural and urban relations.